Last visit was: 13 Jun 2024, 23:46 It is currently 13 Jun 2024, 23:46
Toolkit
GMAT Club Daily Prep
Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History
Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

# If x*y = xy – 2(x + y) for all integers x and y, then 2* (–3) =

SORT BY:
Tags:
Show Tags
Hide Tags
Manager
Joined: 16 Feb 2011
Posts: 142
Own Kudos [?]: 993 [16]
Given Kudos: 9
CEO
Joined: 24 Jul 2011
Status: World Rank #4 MBA Admissions Consultant
Posts: 3187
Own Kudos [?]: 1594 [1]
Given Kudos: 33
GMAT 1: 780 Q51 V48
GRE 1: Q170 V170
Director
Joined: 14 Jul 2010
Status:No dream is too large, no dreamer is too small
Posts: 966
Own Kudos [?]: 4987 [0]
Given Kudos: 690
Concentration: Accounting
Senior Manager
Joined: 01 Feb 2011
Posts: 307
Own Kudos [?]: 327 [0]
Given Kudos: 42
Re: If x*y = xy – 2(x + y) for all integers x and y, then 2* (–3) = [#permalink]
as per the expression 2*-3 = -6-(2*(2-3)) =-4

Target Test Prep Representative
Joined: 14 Oct 2015
Status:Founder & CEO
Affiliations: Target Test Prep
Posts: 19013
Own Kudos [?]: 22400 [0]
Given Kudos: 286
Location: United States (CA)
Re: If x*y = xy – 2(x + y) for all integers x and y, then 2* (–3) = [#permalink]
DeeptiM wrote:
If x*y = xy – 2(x + y) for all integers x and y, then 2* (–3) =

(A) –16
(B) –11
(C) –4
(D) 4
(E) 16

Solution:

2 * (-3) = 2(-3) - 2(2 + (-3)) = -6 - 2(-1) = -6 + 2 = -4

GMAT Club Legend
Joined: 03 Jun 2019
Posts: 5230
Own Kudos [?]: 4066 [1]
Given Kudos: 160
Location: India
GMAT 1: 690 Q50 V34
WE:Engineering (Transportation)
Re: If x*y = xy – 2(x + y) for all integers x and y, then 2* (–3) = [#permalink]
1
Kudos
DeeptiM wrote:
If x*y = xy – 2(x + y) for all integers x and y, then 2* (–3) =

(A) –16
(B) –11
(C) –4
(D) 4
(E) 16

Asked: If x*y = xy – 2(x + y) for all integers x and y, then 2* (–3) =

x*y = xy – 2(x + y)
2*(-3) = 2(-3) - 2(2-3) = -6 + 2 = - 4

IMO C
Senior Manager
Joined: 23 Dec 2022
Posts: 316
Own Kudos [?]: 36 [0]
Given Kudos: 199
Re: If x*y = xy 2(x + y) for all integers x and y, then 2* (3) = [#permalink]
To find the value of 2 * (-3) using the given equation, let's substitute x = 2 and y = -3 into the equation:

x * y = xy - 2(x + y)

2 * (-3) = (2)(-3) - 2(2 + (-3))
= -6 - 2(-1)
= -6 + 2
= -4

Therefore, 2 * (-3) equals -4. Hence, the correct option is (C) -4.
Re: If x*y = xy 2(x + y) for all integers x and y, then 2* (3) = [#permalink]
Moderator:
Math Expert
93696 posts